Perawatan Paliatif terhadap Kualitas Hidup Pasien Kanker Payudara - Irma Nur Amalia; Mia Listia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to identify the effect of palliative care on breast cancer patients' quality of life. The method used in this study is a literature review. The results showed that palliative care affected breast cancer patients. In conclusion, comprehensive palliative care from various aspects of the patient's life plays a significant role in achieving the maximum quality of life in breast cancer patients and preparing for a dignified death. Keywords: Breast Cancer, Quality of Life, Palliative Care